Architectural studies at KTU: objectives, methods, results - Zaleckisa, Kęstutis (Journal of Architecture and Urbanism, 2013)
More than 20 years of independence brought a lot of radical and abrupt changes to society. The sphere of higher education is not an exception. 11 points of European directive 2005/36/EB describe the desired results of architectural studies. During the last decade in the context of the above mentioned results the following problems and challenges in the field of learning quality and teaching methods could be observed: the lack of study process flexibility for deepening of the precise skills necessary for architect; the lack of motivation of students at the beginning of the studies; individualism and lack of team work skills; lack of analytical skills and abilities to evaluate real situation; necessity to develop spatial thinking and artistic skills permanently; lack of professional responsibility and misunderstanding of the architect's role in society, and etc. While developing a systematic approach, architectural studies at Kaunas University of technology are characterized by integrity of: building design, town planning and landscape architecture, academic knowledge and practical skills, scientific research and design decisions, art and technology subjects. Study process, study subjects, assignments for students, and etc. are understood as the elements of one system. In this way, even small changes can have significant consequences for the whole system, i.e. even small improvements of the study program and methods can lead to the efficient solution of these problems. Development of artistic skills and spatial thinking, problem oriented learning, tasks outside curricula, creation of favourable conditions for learning, international students exchange, research and design integration, and etc. provide the missing flexibility of the study program and enable us to solve the various problems that arise in the study process: to eliminate differences of students primary skills, to increase students’ motivation to seek contextual, high quality and interesting architectural solutions, to increase professional responsibility, to develop skills to work in different cultural contexts, and so on.Article in Lithuanian.Architektūros studijos KTU: tikslai, metodai, rezultataiSantrauka. Per daugiau kaip dvidešimt nepriklausomybės metų įvyko nemažai radikalių ir staigių pokyčių visuomenės gyvenime. Aukštojo mokslo sritis taip pat nėra išimtis. 11 Europos Parlamento ir Tarybos direktyvos 2005/36/EB punktų nusako siekiamus architektūros studijų rezultatus. Minėtų rezultatų kontekste per pastaruosius dešimt metų studijų kokybei ir mokymo metodams kyla įvairūs iššūkiai: studijų proceso didesnio lankstumo poreikis siekiant ugdyti specifinius įgūdžius bei reguoti į skirtingus besimokančių asmenų poreikius, studentų motyvacijos stoka studijų pradžioje, individualizmas ir komandinio darbo gebėjimų, analitinių ir realios situacijos vertinimo įgūdžių trūkumas, būtinybė nuolatos vystyti erdvinį mąstymą ir meninius gebėjimus, profesinės atsakomybės stoka bei architekto vaidmens visuomenėje nesuvokimas ir kt. Stebint ir vertinant studijų proceso kokybės pokyčius Kauno technologijos universitete galima teigti, kad ir nedideli studijų programos ir metodų patobulinimai gali lemti efektyvų minėtų problemų sprendimą. Meninių gebėjimų ir erdvinio mąstymo ugdymas, į problemos sprendimą orientuotas mokymas, papildomos užduotys, palankios darbui ir mokymuisi atmosferos sukūrimas, tarptautiniai studentų mainai, mokslinių tyrimų ir projektavimo integracija ir kt. suteikia studijų programai trūkstamo lankstumo ir leidžia operatyviai spręsti įvairias problemas, kylančias studijų procese: panaikinti studentų pradinių gebėjimų skirtumus, didinti studentų motyvaciją ieškoti kontekstualių, kokybiškų ir įdomių sprendimų, didinti profesinę atsakomybę, ugdyti gebėjimus dirbti įvairiuose kultūriniuose kontekstuose ir kt.Reikšminiai žodžiai: Kauno technologijos universtitetas, architektūros studijos, metodai.